(3efJNHGJ ef GdLhGgQ GdNeSs - (3eMeO Hf NWjQ Hf HGjRjO GdYWGQ, GHf NWjQ GdOjf , CHh GdeDjO,J (B970 (3g` s
(3ChdgG (B:s
(3OYhI GdSeGA hGdYXGe hTQGjWgG hEf cd OGY eLGH GdOYhI s
(3BNQgG (B:s
(3dGJMUi dcf aj GdCWhGQ hGdCdhGf jZdH WhQkG Ydi SGFQ GdCWhGQ MJi jYOege cXghQ GdTeS HYOe GdfLhe s
(3GdfSNI HgG MhGTs
(3GfXQ GdLhGgQ GdNeS ai cTa GdXfhf L (B1 (3U`(B614s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B114 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B282s
Keywords: (3GdJUha hGdBOGH GdTQYjIs